Hubungan Dukungan Sosial dengan Stress Akademik pada Mahasiswa Psikologi Universitas Negeri Padang - Adrian, Afiful; Putri, Emilya Dwinata; Fitri, Raudhatul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research was conducted to determine the relationship between social support and academic stress on psychology students at UNP. The method used is quantitative research with a correlation approach. The sample of this research was 63 students who were taken using purposive sampling method. Data analysis used the pearson product moment correlation test. The results of this study indicate that there is a significant negative relationship between social support and academic stress. Students who get low social support report high levels of academic stress, students who get low social support report high levels of academic stress.